EPOXY COATING REINFORCED WITH GO-ZNO AS COATINGS FOR THE PROTECTION AGAINST HIGH-PRESSURE CO2 GAS ENVIRONMENT - OTHMAN, NURUL HUSNA (2021)
The oil and gas industry offers challenging applications for corrosion protection systems and demands chemical and mechanical resistance, toughness and long-term reliability. The requirements for a robust, cost-effective and stable internal coating can be achieved by the emerging graphene technology. Due to its exceptional lamellar structure, graphene and its derivatives have been certified as anticorrosive additives to improve the formulation of polymeric coatings. However, the performance of graphene and its derivatives are limited due to the severe stacking state of sheets and their poor interfacial interaction between most polymers. The lack of study in high-pressure carbon dioxide gas environment typical of environment in oil and gas pipelines limits the applications of such fillers as derivatives for internal coatings.